2012
DOI: 10.1155/2012/789274
|View full text |Cite
|
Sign up to set email alerts
|

Morning Cortisol Levels and Perceived Stress in Irregular Shift Workers Compared with Regular Daytime Workers

Abstract: The 24/7 work environment and irregular shifts may markedly enhance the psychological pressure of media work. Changes in the hypothalamic-pituitary-adrenal axis reflect adaptation to stress. We analysed the correlation between subjective stress, sleep, salivary cortisol, and melatonin hormones among Finnish media workers with regular daytime work (RDW) and with irregular shift work (ISW) while controlling confounders. From 874 employees with regular daytime work or with irregular shift work, 70 employees from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 37 publications
0
22
0
2
Order By: Relevance
“…In our study, examinations and blood tests that followed the night shift were performed 15 min earlier on average than those prior to the shift (average time pre night shift: 10:18 hours; average time post night shift: 10:03 hours); this small difference should not suffice to significantly affect results. It could be shown that a stressful work environment and irregular shift work enhances cortisol excretion after waking (Lindholm et al., ). Most of the study subjects were able to sleep in the morning hours just before the completion of their shifts, thus the detected increase in cortisol levels may be related to the cortisol awakening response (Fries, Dettenborn, & Kirschbaum, ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, examinations and blood tests that followed the night shift were performed 15 min earlier on average than those prior to the shift (average time pre night shift: 10:18 hours; average time post night shift: 10:03 hours); this small difference should not suffice to significantly affect results. It could be shown that a stressful work environment and irregular shift work enhances cortisol excretion after waking (Lindholm et al., ). Most of the study subjects were able to sleep in the morning hours just before the completion of their shifts, thus the detected increase in cortisol levels may be related to the cortisol awakening response (Fries, Dettenborn, & Kirschbaum, ).…”
Section: Discussionmentioning
confidence: 99%
“…The interval between 8ASC and diagnosis of DDD in our outpatient department was strictly controlled within 3 days. The case who had reverse day and night life would be excluded from our research for disturbed cortisol circadian . Any medical record with incomplete variables would be excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Generally, the serum cortisol reaches the peak in the early morning for its circadian nature. The serum cortisol of 4 and 10 PM may be influenced by daytime activity because the serum cortisol usually response to acute stressful stimulus or events (11). The 8 AM serum cortisol level (8ASC) has demonstrated an intensely positive correlation with stress, depression and pain (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…Cortisol (dexamethasone), which is high in the early morning, elevated in stressful constant light conditions (110) but reported to be both elevated (111) and reduced (112) in the morning in shift-workers, possibly depending on the degree of experienced stress in the individual (111), is a more clear-cut inhibitor of angiogenesis. Cortisol inhibits pathological VEGF-A production in tumors (113) as well as physiological VEGF-A production in growth plate chondrocytes (114) and vascular smooth muscle cells (115).…”
Section: Angiogenic Functions Of Circadian Factors or Output Moleculesmentioning
confidence: 99%